Perception Of The Second Year Students On The Importance Of Learning English At The Department Of PTIK - Lailatul Husna; Nuralita Nuralita (Innovative: Journal Of Social Science Research, 2023)
This research aimed to find out the second year students’ perception on the importance of learning English at the department of PTIK FKIP UBH. The method of this research is descriptive research. The population of this research is the second year students of PTIK. The number of samples was 18 students taken by the total sampling technique. The data were taken by using a questionnaire. Based on the results of the data analysis, it can be concluded that in general, the students of PTIK think that English is an important subject. It can be seen in the high index that is found on the result of data analysis. It can be concluded specifically, first, the students’ perception about the importance of Learning English is positive and the index is 86.11%, it is categorized as a good/positive response. Second, the students’ perception about the importance of learning English language skills is positive and the index is 86.11%, it is categorized as a good/positive response. Based on the result of the research, it was found that the students of PTIK think that English is an important subject. The researcher would like to give some suggestions to the lecturers to guide the students in learning English and teach the students to have better English. The students are suggested to pay attention to the lecturers while teaching, so the students will have better English